Modern weapons and military equipment 04-2025 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2025)
ALERT: Russia Deploys New A-222M Bereg Coastal Artillery to Pacific Fleet Amid Rising Tensions in Asia-Pacific US Navy Showcases Long-Range Strike Capability with AIM-174B Missile in Japan to Counter Chinese Threat Alert: New Russian KS-172 Air-to-Air Missile Extends MIG-31s Engagement Range to 400 km.